1978
DOI: 10.1017/s0021859600056653
|View full text |Cite
|
Sign up to set email alerts
|

Water relations of winter wheat: 1. Growth of the root system

Abstract: SummaryThe production of root axes and the growth of the root system are reported for a commercially grown crop of Maris Huntsman winter wheat. Soil cores were extracted on 17 occasions during the growing season permitting a detailed study of root length and root dry weight with depth and time.Production of seminal root axes was complete by the beginning of March when all plants possessed six (occasionally seven) axes which persisted throughout the life of the crop. Nodal axes were produced continuously from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
150
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(170 citation statements)
references
References 23 publications
20
150
0
Order By: Relevance
“…Winter wheat rooting depth at harvest was around 2 m, twice the depth we found for spring wheat. Similar depths of winter wheat have previously been shown (Gregory et al 1978) whereas Kirkegaard and Lilley Error bars indicate standard error (n=3). Abbreviations: WW, winter wheat; WWe, early sown winter wheat; SW, spring wheat; FR, fodder radish; HV, hairy vetch; T, turnip; CV, common vetch; O, oats; BS, bare soil (2007) and Anderson et al (1998a) found lower depths of around 1.6-1.8 m. Root depths of spring wheat were similar to those found by Kirkegaard and Lilley (2007).…”
Section: Root Differences In Spring Wheat and Winter Wheatsupporting
confidence: 80%
See 1 more Smart Citation
“…Winter wheat rooting depth at harvest was around 2 m, twice the depth we found for spring wheat. Similar depths of winter wheat have previously been shown (Gregory et al 1978) whereas Kirkegaard and Lilley Error bars indicate standard error (n=3). Abbreviations: WW, winter wheat; WWe, early sown winter wheat; SW, spring wheat; FR, fodder radish; HV, hairy vetch; T, turnip; CV, common vetch; O, oats; BS, bare soil (2007) and Anderson et al (1998a) found lower depths of around 1.6-1.8 m. Root depths of spring wheat were similar to those found by Kirkegaard and Lilley (2007).…”
Section: Root Differences In Spring Wheat and Winter Wheatsupporting
confidence: 80%
“…However, if winter wheat has significant root activity and N uptake from soil layers between 1 and 2 m depth, its effect on N leaching losses may be significantly better than often assumed. Growth of wheat roots has been observed to more than 1.8 m (Gregory et al 1978;Kirkegaard and Lilley 2007;Sauer et al 2002). N placed in different depths up to 1.5 m, gradually affected N uptake from winter wheat (Daigger and Sander 1976), suggesting presence of roots in deeper layers, though maybe not sufficient for taking all N from these soil layers.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, since the root system of wheat often fails to take up all the available deep soil water because root growth stops owing to the lack of available time (Passioura 1983). Root growth runs out of time because it often slows down when less photosynthetic fixed carbon is invested in root growth from ear initiation (Davidson et al 1990;Palta and Gregory 1997) and ceases from flowering when grain filling becomes the major sink for carbon from current assimilation and stem reserves (Gregory et al 1978). Consequently, root proliferation and elongation of the seminal roots before flowering is critical in increasing the capture of available deep water, although post-flowering root growth in wheat has been observed in the cultivar SeriM82 (Manschadi et al 2006).…”
Section: Invigorating the Root System In Wheat Is Increasing Its Sizementioning
confidence: 99%
“…Microporosity was not altered and total porosity was diminished, showing that only macroporosity is affected by soil compaction (Dias JR & Pierce, 1996). Plant water availability is important in soil compaction experiments because of the interaction with the factor under study (Gregory et al, 1978). To avoid that, volumetric water content (Table 1) was maintained close to field capacity (previously determined), even in the higher soil bulk density.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, roots were less effective in exploring the soil, decreasing water and nutrient interception and absorption as well as diminishing their supply to shoot, important factors associated with reduced plant growth in compacted soils (Gregory et al, 1978).…”
Section: Resultsmentioning
confidence: 99%